2015
DOI: 10.1016/j.vetmic.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of mefloquine on feline calicivirus in vitro

Abstract: Feline calicivirus (FCV) is an important viral pathogen of domestic cats causing clinical signs ranging from mild to severe oral ulceration or upper respiratory tract disease through to a severe fatal systemic disease. Current therapeutic options are limited, with no direct acting antivirals available for treatment. This study screened a panel of 19 compounds for potential antiviral activity against FCV strain F9 and recent field isolates in vitro. Using a resazurin-based cytopathic effect (CPE) inhibition ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
(38 reference statements)
1
28
0
Order By: Relevance
“…Combination antiviral therapy has become a common practice. Recently, researchers revealed that a combination treatment of rFeIFN-ω and mefloquine resulted in additive effects with a reduction in the half maximal inhibitory concentration [79]. Another study conducted by Lee et al [80] showed that the relative expression of IFN-ω, Mx, and ZAPS mRNA in Crandell-Reese Feline Kidney cells was upregulated significantly in FCV-infected cats.…”
Section: Fcv and Fhv-1mentioning
confidence: 99%
“…Combination antiviral therapy has become a common practice. Recently, researchers revealed that a combination treatment of rFeIFN-ω and mefloquine resulted in additive effects with a reduction in the half maximal inhibitory concentration [79]. Another study conducted by Lee et al [80] showed that the relative expression of IFN-ω, Mx, and ZAPS mRNA in Crandell-Reese Feline Kidney cells was upregulated significantly in FCV-infected cats.…”
Section: Fcv and Fhv-1mentioning
confidence: 99%
“…Confluent CRFK cell monolayers in 96-well plates (10 4 cells) were incubated overnight at 37°C and 5 % CO 2 in complete medium. The cell supernatant was removed, and the monolayers were overlaid with 100 lL of LiCl at a series of concentrations (20,40,60, 80 and 100 mM) in serum-free DMEM for 24 h and 72 h; the monolayers were then washed with PBS. Mock-treated CRFK cells served as a control.…”
Section: Cytotoxicity Assay For Liclmentioning
confidence: 99%
“…Feline-calicivirus-specific antiviral phosphorodiamidate morpholino oligomers (PMO) were tested in naturally occurring outbreaks of FCV, and the results demonstrated that PMO can work as a high-efficiency drug to treat FCV disease [30]. Mefloquine was employed as monotherapy or combination treatment with rFeIFN-x [20], but deficiencies in a number of drug metabolism pathways have been recognized in humans [20]. For more than fifty years, lithium chloride (LiCl) has been used as a major treatment for bipolar disorder [18], and the mechanisms of LiCl have been explored, particularly for treating Alzheimer's disease [10], diabetes [16], and serous ovarian cancer [21], and also as an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…To further evaluate the anti-FCV activity, the resazurin-based CPE inhibition assay as described previously [5] was used. Titration of IOP showed a concentration-response relationship, showing nearly 80% inhibition of the cytopathic effect (CPE) at a concentration of 100 g/mL and 30% inhibition at a concentration of 10 g/mL when the cells were infected at an MOI of 0.005 (Fig.…”
Section: Iop Inhibits Fcv Strain F9 Replication In Vitromentioning
confidence: 99%